DEVELOPMENT MODULE OF ACID BASE BASED ON MULTIPLE REPRESENTATIONS - erika octaviani; chansyanah diawati; nina kadaritna (Universitas Lampung, 2012)
Chemistry is one of knowledges that learn abstract phenomena and difficult to understand by students generally and chemical learning at this momen only in makroscopic and symbolic dimension, whereas submicroscopic often deserted. The research aim to develop module of multiple representation based on the acid base material.Method used on this research is research and development (R D) according to Sukmadinata (2009). But on this research, step only arrive to step of main product revision. Research and development on this research have three steps. There are step 1st) needs analysis that consist of literature study and field study, step 2nd ) planning and development that consist of planning preliminary product, develop preliminary product,validation, and preliminary product revision, step 3th) preliminary field test, and main product revision.Results of this research is development module of acid-base based on multiple representations which have characteristic: 1) module refers to the SK and KD, 2) material packaged in units of learning activities, modules arranged in a systematic and attractive, giving rise to interest in reading to students, 3) the material presented in the modules developed chemical, described by multiple representations, 4) accompanied by examples and illustrations that support the material, 5) the language used is simple and communicative, 6) have level of contents suitability is very high that is 82 % and have level of aspects graph 86,35 % according to teacher, also have high level of legibilityt is high that is 79,26% according students.Key words : module, multiple representation, the chemical acid base material